Help-seeking patterns in an Egyptian sample of substance use disorder patients. Issue 3 (July 2016) - Zaki, Nivert; Soltan, Marwa; Hashem, Reem E.S.; Elwasify, Mohamed; Elwasify, Mahmoud; Elturky, Jehan
Abstract : Background: Substance use disorder is a major problem worldwide. The increased number of addicts is not matched by an equal effort to increase awareness of the available services provided to them in their community. Patterns of seeking help and sources of advice and referral to specialized and professional help are not clear and quiet related to the cultural and demographical environment, something that had never been properly investigated in the Egyptian community. Aim: This study explored the most frequent patterns of help-seeking behaviors among patients with substance use disorders and the referral sources to professional services. Participants and methods: This cross-sectional, questionnaire-based observational study was conducted among 40 patients aged above 18 years who were diagnosed with substance use disorder according to DSM-IV and who presented at the substance treatment program with male residential and outpatient services at the Institute of Psychiatry of Ain Shams University Hospitals over a period of 6 months. Exclusion criteria were limited mental competency, intoxication, or the inability to provide informed written consent. The data were gathered using Fahmy and El-Sherbini's Social Classification Scale, Addiction Severity Index, and a Researcher-Designed Questionnaire and were analyzed using SPSS software. Results: The primarily abused drug was tramadol, a seen in 70% of the sample, followed by heroin in 20% and other substances including alcohol in 12.5%. Family was the most frequent source of referral to professional help among cases attending the clinic, and emergency services was the least common. The mean severity profile scores measuring problems and functional impairment using Addiction Severity Index were higher in the 'employment' domain (0.66±0.32), whereas legal (0.00±0.00), alcohol (0.01±0.07), and psychiatry (0.01±0.06) domains had lower scores. Our study concluded that patients who presented late for help (>1 year) were mostly divorced, living in slum areas, and were middle class. We also found that they first approached their friends for consultation, and source of referral was emergency room or friends with the same problem. Conclusion: Help-seeking through family was the most common pattern in our study.